Attention to disability in child protection policies across four liberal welfare regimes. - Flynn, Susan (My University, 2025)
How child protection and welfare policies address the disability community is a matter of utmost importance and urgency in the context of well-established inequalities. We present a policy content analysis of national policy documents across the United States, Northern Ireland, Australia and the Republic of Ireland through the theoretical frame of a welfare regimes typology. Key findings include the conflation of disability with vulnerability in all but one context. Also evident is a lack of overt definition of disability, and opportunities for developing specific jurisdictional guidance and regulations focussed on embedding best practices in supporting disabled clients at all system levels.
PUBLISHED
https://doi.org/10.1080/15548732.2024.2306165
Keywords: Disability; Child protection; Child welfare; Policy; Legislation